Advancement of the Harrington technique for reconstruction of pathological fractures of the acetabulum. (2nd October 2018) - Coomber, Ross; Lopez, D'Jon; Carrothers, Andrew D
Abstract : A 59-year-old man presented with hip pain secondary to metastatic prostate carcinoma affecting multiple sites, including his left acetabulum. The patient's prognosis was good, he was active, independent, with a good quality of life, so was offered surgical reconstruction. The Harrington method involves passing metal rods from the ileum to the ischium and pubis to create a scaffold for hip replacement. This is the gold standard for reconstruction of acetabular metastatic defects. However, this method is prone to failure by medialisation of the construct in the long term. We present our technique of employing a novel modification to the Harrington reconstruction that offers additional support medially with a suprapectineal plate. This construct is strong and durable enough to facilitate immediate weight-bearing and prevent long-term medialisation.